Emphysematous Pyelonephritis in A Young Female presenting as Abdominal Pain & Swelling - Khan Md Nazmus Saqeb; Hiba Malik (Bangladesh Critical Care Journal, 2025)
Background: Emphysematous pyelonephritis (EP) is a severe necrotic infection of the kidney by gas forming organisms, characterized by the presence of gas within the renal parenchyma. The risk factors for developing emphysematous pyelonephritis (EP) include uncontrolled diabetes mellitus, obstruction of the urinary tract, and immunosuppression. The most frequent organism identified on culture is Escherichia Coli. Case Report: We report a case of a patient who was admitted with the symptoms of abdominal pain and swelling with fever for 2 weeks. Imaging revealed gas in the renal parenchyma establishing the diagnosis. The patient was treated initially with antibiotics & percutaneous drainage but as the condition deteriorated, surgical removal of the affected kidney was necessary. Conclusion: Emphysematous pyelonephritis is a medical emergency, and a high degree of suspicion is needed once pyelonephritis is not responding properly to antibiotics alone. An early diagnosis and prompt initiation of treatment is a must to reduce mortality. Bangladesh Crit Care J March 2025; 13 (1): 62-64